Antimicrobial activity of plant extracts on self-service restaurant salad fertilizers (Research, Society and Development, 2022)
This study aimed to evaluate the microbiological quality of salads sold in self-service restaurants, as well as to determine the antimicrobial activity of extracts from three different plants against bacteria isolated from the samples of the present study. The parts from the plants were submitted to the maceration process. The extracts from the oregano came from the aerial parts, from the saffron the extract came from the rhizome and from the guava plant the extract came from the leaves. The determination of coliforms at 45°C and the identification of the Enterobacteriaceae family in the analyzed salads were performed. The percentage yield was determined from the dry material, the content of total phenolics was determined by the colorimetric method using Folin-Ciocalteau reagent. The results indicated the presence of species of the Enterobacteriaceae family in the analyzed salads. Guava leaf extracts showed the highest quantification of total phenolics. Regarding the antibacterial activity, the plant extracts showed bactericidal action against the tested strains.